LEGAL PROTECTION OF YEI PEOPLE'S KNOWLEDGE OF LOCAL MEDICINES AND MEDICINAL PLANTS FROM EXTINCTION - Purwanda, Sunardi; Rado, Rudini Hasyim; Susanti, Diana Sri; Zainuddin, Asriadi; Syahril, Muh. Akbar Fhad (Faculty of Law, Universitas Diponegoro, 2024)
Food security investments have brought conflict between local indigenous communities and the government in South Papua. The research aims to encourage protection and recognition efforts from the state towards indigenous peoples' entities. This research uses socio-legal studies. The research found sixteen plants that function as medicine. Inventory in the form of